PERANCANGAN DAN MODIFIKASI MOLD INSERT UNTUK MENINGKATKAN KAPASITAS PRODUKSI LIGHT GUIDE - Irawan, Benny Haddli; Septaningrum, Putri; Wijayanti, Ita; Hakim, Rahman; Saputra, Ihsan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The use of plastic is often found in human life. Therefore, many manufacturing companies are competing to increase the production and quality of their plastic products. One way to increase production is to redesign a Mold base so that the Mold has a larger production capacity than before. The increase in product demand from consumers, which was initially 65,000 pcs/month to 95,000 pcs/month, is also the background for conducting this research. The purpose of this study is to redesign the soft tool using the old Mold base. The design uses Siemens UG NX 5 software. The Mold used is a two-plate Mold. The manufacture of the core cavity uses NAK 80 steel and plastic raw material in the form of Polycarbonate (PC). At the end of the study, a simulation was carried out using the Moldex 3D Flow Mold software to see the cycle time of the old and new Mold injection processes. From the results of this study, production capacity increased from 67,804 pcs/month to 118,536 pcs/month resulting in twice as many products as the old Mold design, with an increase in cycle time of 14.37% longer than the old Mold design also ensuring the quality of the product is maintained.